The effect of grafting on vegetative and reproductive traits of tomato - Sh. N. Rajametov; Hyo-Bong Jeong; Eun-Young Yang; Myeong-Cheoul Cho (Овощи России, 2024)
Relevance. Tomato (Solanum lycopersicum L.) is one of the most important vegetables in the world. Every year the number of identified viruses and diseases increases, infection with which causes significant crop losses and significantly worsens the quality of agricultural products, especially in tomatoes.   Material and methods. In the present study we compared the growth of the vegetative and reproductive traits of tomato plants ‘Dokia’, ‘TY Red 250’ and ‘Pilabi’ grated onto bacterial wilt (caused by Ralstonia solanacearum) and Fusarium wilt (Fusarium oxysporum) diseases tolerant rootstock “Spider” (Takii seed, Japan). The non-grafted (control - CT) and grafted tomato plants (GR) were transplanted on 4 March of 2021 to the four season (vinyl) greenhouse on substrate perlite (mixture of perlite no. 1 and no. 3) and cultivated until September 20.   Results. The results showed that responses of the tomato cultivars to grafting combination was different, where agronomical traits depends on the each cultivar’s features can be ranged. The reduction of the values of stem diameter (SD), leaf length and width (LW), fresh fruit weight (FFW), fruit diameter (FD), fruit pericarp thickness (FPT) and fruit hardness (FH) with aging of plants and rising ambient temperature was detected. However, fruit soluble solids among all cultivars regardless of treatments were slightly increased. The index of fruit yield per truss (FYT) significantly decreased among all cultivars after 10th truss regardless of the treatments when the daily temperature increased from July to August. In grafted tomato ‘TY Red 250’ were identified the highest fruit yield per plants (FYP) than in CT plants, whereas in other tomatoes did not found similar differences between CT and GR plants.